2012
DOI: 10.1111/j.1728-4465.2012.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Calendar Data for Reporting Contraceptive Use: Evidence from Rural Bangladesh

Abstract: Collecting contraceptive-use data by means of calendar methods has become standard practice in large-scale population surveys, yet the reliability of these methods for capturing accurate contraceptive histories over time remains largely unknown. Using data from overlapping contraceptive calendars included in a longitudinal study of 3,080 rural Bangladeshi women, we assessed the consistency of reports from the baseline interview month in 2006 with reports from the same month in a follow-up survey three years la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 33 publications
(51 reference statements)
3
57
1
3
Order By: Relevance
“…Lastly, this analysis uses women’s self-report of the timing of their pregnancies in the 5 years prior to interview. While interviewers use cues to improve the accuracy of these self-reports, 38 as with any study that involves recall, this study is subject to bias. A study in Bangladesh found that women who have experienced the highest numbers of pregnancies over the recall period may be least likely to accurately report those pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, this analysis uses women’s self-report of the timing of their pregnancies in the 5 years prior to interview. While interviewers use cues to improve the accuracy of these self-reports, 38 as with any study that involves recall, this study is subject to bias. A study in Bangladesh found that women who have experienced the highest numbers of pregnancies over the recall period may be least likely to accurately report those pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Although calendar data do not suffer from the problem of loss-to-follow-up, there is a selection bias as only women who survive until the interview can report, and there are likely to be recall issues. One study from Bangladesh found poor consistency between reports given in a baseline interview and reports given in a follow-up survey in which women were asked to describe retrospectively their contraceptive use during the month covered by the baseline survey; 7 consistency was especially poor for women with complex reproductive histories. Single-country studies on contraceptive discontinuation and switching, based on data from sources other than demographic and health surveys, are uncommon because such data tend to be difficult to collect and analyse.…”
Section: Introductionmentioning
confidence: 99%
“…However, the small number who did not complete the second survey were significantly younger and of lower parity than those completing both surveys. A description of women lost to follow-up 20 and additional details of the experimental study and study design are reported elsewhere. 21 Women were eligible for the present analysis if they completed both BMHS survey rounds and were married and between the ages of 13-49 at baseline; the final sample totaled 3,024 women.…”
Section: Samplementioning
confidence: 99%